2014
DOI: 10.1371/journal.pone.0106888
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Initiation but Not Gradual Advancement of Enteral Formula Feeding Reduces the Incidence of Necrotizing Enterocolitis (NEC) in Preterm Pigs

Abstract: Enteral formula feeding is a risk factor for necrotizing enterocolitis (NEC) in premature infants, yet studies are conflicting regarding the safest timing for introduction and advancement of feeds. Our aim was to test the effects of early vs. late initiation and abrupt vs. gradual advancement of enteral feeding of an intact vs. hydrolyzed protein formula on NEC incidence and severity in preterm pigs. In Experiment 1, preterm pigs received total parenteral nutrition (TPN) at birth with abrupt initiation of ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Regardless, the middle and distal small intestine is consistently affected when NEC progresses to more severe stages in preterm pigs (7). Our results are consistent with another recent study in preterm pigs showing that early gradual advancement of enteral formula induces NEC and that delayed formula introduction (until after day 5) decreases NEC incidence (23). The "subclinical NEC phenotype" in our study may be similar to the clinical situation in many preterm infants, where early diagnosis is difficult and limited to X-rays or noninvasive means such as increased gastric residuals (i.e., feeding intolerance).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regardless, the middle and distal small intestine is consistently affected when NEC progresses to more severe stages in preterm pigs (7). Our results are consistent with another recent study in preterm pigs showing that early gradual advancement of enteral formula induces NEC and that delayed formula introduction (until after day 5) decreases NEC incidence (23). The "subclinical NEC phenotype" in our study may be similar to the clinical situation in many preterm infants, where early diagnosis is difficult and limited to X-rays or noninvasive means such as increased gastric residuals (i.e., feeding intolerance).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in both preterm pigs and infants have shown that rapid advancement of feeding with infant formula induces NEC (6,15,23). This supports the general practice to initially feed very small volumes before advancing feedings gradually.…”
supporting
confidence: 68%
“…The incidence of NEC across developed countries is ;5-12% for VLBW infants (13)(14)(15)(16)(17)(18), depending on certain risk factors. Three major risk factors for NEC are <32 wk gestational age, <1500 g at birth, and cardiac complications (10).…”
Section: Necmentioning
confidence: 99%
“…Last, there are distinct differences between term and preterm infants in regard to the expression of immune cells and signaling pathways. A preterm immune system cannot readily detect pathogens and protect against infections due to multiple associated factors such as 1) the decreased production of IgA, IgM, IgG, and defensins; 2) changes in the expression of toll-like receptors (TLRs), especially TLR4 and TLR9, which are involved in pathogen recognition and the activation of the innate immune system (14,28,29); and 3) upregulation of proinflammatory TLRs (26) and/or proinflammatory cytokines such as TNF-a, IL-6, IL-8, and IL-1b (26,27). The culmination of these factors increases a preterm infant's vulnerability to infections and disease, particularly NEC.…”
Section: Necmentioning
confidence: 99%
“…Early GI maturation may help to prevent later adverse effects of slow growth and inadequate nutrient intake in preterm infants (30). On the other hand, too rapid advancement of enteral feeding is associated with high NEC risk, and delayed advancement of enteral feeding may decrease NEC risk in both preterm infants and pigs (20,32,33). Consequently, a gradual introduction of mother's own milk, donor milk, or infant formula ("minimal enteral nutrition," daily increases of 10 -20 ml·kg Ϫ1 ·day Ϫ1 ), is often used for 1-2 wk after birth as adjunct to parenteral nutrition (PN), before transition to full enteral feeding at 2-4 wk (e.g., 150 -180 ml·kg Ϫ1 ·day Ϫ1 ).…”
mentioning
confidence: 99%